A transexualidade e sua repercussão no registro civil brasileiro: da possibilidade de alteração do nome e do sexo independentemente da cirurgia de transgenitalização, como concretização do direito à identidade - Costa, Marina Aguiar da (2015)
It analyses the civil legal treatment provided to transsexual people concerning the Public Records. It aims to investigate the possibility of transsexual people changing their legal name and gender, regardless of sex reassignment surgery, in pursuance of fulfilling their right to personal identity. It approaches the right to a name and the right to gender identity from the standpoint of the personality rights, and as branches of the right to personal identity. Furthermore, it proposes a multidisciplinary analysis of transsexuality: it exposes etiologic theories, concepts, and definitions of transsexuality according to the medical, psychological, and sociological sciences. Additionally, it questions if the sex reassignment surgery influences in the personal identity perception of oneself, and how the Comparative Law receptions the register change of transgender people. It utilizes analysis of draft bills that aim to safeguard Trans people, the social name purpose, and Brazilian case law about name and gender change in the birth certificate. It concludes that the concessions of requests regarding legal name and gender change is feasible and necessary, as a way to allow their legal identity to match their inner truth, guaranteeing to them knowledgeability. It comprehends, moreover, that the issuing of legislation that disciplines the thematic is needed, since the lack of regulation leads to different judicial decisions to transsexual citizens in equal situations.